Pengaruh Brexit Bagi Ekonomi Uni Eropa di Masa Transisi Tahun 2020 - Jalu Tunjung Widura (Solidaritas: Jurnal Ilmu-Ilmu Sosial, 2022)
The European Union is one of the largest supranational organizations in the world, and the UK is a member of it. At first the relations between the UK and the European Union were going well, until in the end the UK considered the EU policies detrimental to the UK and the UK chose to leave the EU or known as BREXIT. Based on this problem, researchers are interested in researching how the influence of BREXIT in the economic field on the European Union during the transition period in 2020. The European Union is one form of international cooperation which in this case must continue to be built to create the economic conditions of the European Union during the BREXIT transition through activities international economy. The research method used is qualitative research with secondary data sources obtained from the official web and news. The existence of BREXIT brings its own impact on the European Union economy. BREXIT member countries had to create a collective fund to cover the UK's contribution fund, the European Union also lost some of investors during the transition. The European Union seeks ways for the European Union to survive in the Brexit transition period, where at this time the European Union has suffered many losses but is still trying to maintain its organizational integration.Keywords: Brexit, European Union, International Cooperation, International Economy, UK